2022
DOI: 10.1093/cid/ciac176
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Effectiveness Outcomes From a 14-Country Cohort of Patients With Multi-Drug Resistant Tuberculosis Treated Concomitantly With Bedaquiline, Delamanid, and Other Second-Line Drugs

Abstract: Background Concomitant use of bedaquiline (Bdq) and delamanid (Dlm) for multi-drug/rifampicin resistant tuberculosis (MDR/RR-TB) has raised concerns about a potentially poor risk-benefit ratio. Yet, this combination is an important alternative for patients infected with strains of TB with complex drug resistance profiles or who cannot tolerate other therapies. We assessed safety and treatment outcomes of MDR/RR-TB patients receiving concomitant Bdq and Dlm, along with other second-line anti-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 20 publications
1
10
0
1
Order By: Relevance
“…[20] A study by Huerga et al demonstrated that 358/458 patients (78.0%) had a favorable outcome in a regimen containing bedaquiline-delamanid. [21] Compared to the study by Phuong et al, reported in patients with RR-TB who received five drugs of STR (bedaquiline, levofloxacin, linezolid, clofazimine, and/or pyrazinamide), the successful treatment was 95/106 (90%). Meanwhile, unfavorable outcomes including treatment failure, death, and loss of follow-up were 4%, 1%, and 6%, respectively.…”
Section: Efficacy Of Bpal Regimenmentioning
confidence: 84%
“…[20] A study by Huerga et al demonstrated that 358/458 patients (78.0%) had a favorable outcome in a regimen containing bedaquiline-delamanid. [21] Compared to the study by Phuong et al, reported in patients with RR-TB who received five drugs of STR (bedaquiline, levofloxacin, linezolid, clofazimine, and/or pyrazinamide), the successful treatment was 95/106 (90%). Meanwhile, unfavorable outcomes including treatment failure, death, and loss of follow-up were 4%, 1%, and 6%, respectively.…”
Section: Efficacy Of Bpal Regimenmentioning
confidence: 84%
“…The mixture was degassed and refilled with Ar gas several times. After stirring at 60 °C overnight, the mixture was purified to give the desired product 7 (76%) as a white solid: R f = 0.52 (MeOH: DCM, 1.0:9.0, v/v); 1 (8). To a solution of (S)-5-(aminomethyl)-3-(4-bromo-3-fluorophenyl)oxazolidin-2-one (1.0 equiv), 2-(methylsulfonyl) pyridine-5-boronic acid (1.2 equiv), and potassium phosphate tribasic (2.0 equiv) in THF (1M) was added the second-generation XPhos precatalyst (0.1 equiv) under an Ar atmosphere.…”
Section: S)-4′-(5-(aminomethyl)-2-oxooxazolidin-3-yl)-2′-fluoro-[11′-...mentioning
confidence: 99%
“…Oxazolidinone antibiotics such as linezolid are known to be efficacious for the treatment of tuberculosis (TB) through clinical studies of patients with a highly drug-resistant disease. Unfortunately, linezolid has an unacceptable side-effect profile upon prolonged exposure, limiting its use in TB to only the most drug-resistant cases. Such side-effects include bone marrow suppression, painful peripheral neuropathies, and optic neuropathies and are thought to be mechanism-related. Although these side-effects are often reversible with careful management, they effectively limit the use of linezolid to the population of patients infected with a highly drug-resistant disease. Linezolid inhibits protein synthesis by binding to the 50S ribosomal subunit involved in bacterial protein synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…There was one sudden death in this group and two other potential participants in the cohort also died suddenly with no prior evidence of QTc prolongation but neither occurred in participants on both drugs. Non-TB co-medication and electrolyte disturbance were identified as potentially important additional risk factors and the authors suggested that more evidence-based strategies for risk-stratified ECG monitoring are needed [20 ▪ ,21 ▪ ].…”
Section: Delamanid: the First Nitroimidazooxazinementioning
confidence: 99%